WHICH DIMENSION OF THE HOFSTEDE CULTURAL VALUE AS THE MOST DETERMINING PREDICTOR TO THE DIFFERENCES IN ORGANIZATIONAL BEHAVIOR - Zakhyadi Ariffin (JWM (JURNAL WAWASAN MANAJEMEN), 2020)
This study aimed to investigate which dimensions of national cultures of the Hofstede’s Cultural Values was the most predictors of differences in organizational behavior between countries. Hofstede’s cultural values are the framework for national cultural values that most researchers and managers refer to in organizational practice. The framework of Hofstede's national cultural values involves six dimensions include power distance, individualism-collectivism, masculinity-femininity, uncertainty avoidance, long-term-short-term orientation, and indulgent-restraint. A systematic literature review was used as a method in this study. The research results selected for review were researches published in widely recognized international scientific journals in English and dissertation research from internationally recognized universities. Data analysis used a matrix to obtain conclusions in response to the research question. The findings of this study showed that the individualistic-collectivistic dimension formed the national cultural one that was most widely proven as a determinant of behavioral differences in organizations between countries. However, the individualistic-collectivistic dimension cannot be concluded that dimensions of Hofstede's national culture are the ones that most determine the differences in organizational behavior between countries because the studies conducted did not examine all dimensions of national culture on organizational behavior.